A prospective study of sinonasal and nasopharyngeal pathology in chronic otitis media - K. B., Sajitha; Thomas, Binu; A. T., Ihsan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Chronic otitis media (COM) implies a permanent abnormality in the tympanic membrane characterized by irreversible changes in the mucosa of middle ear and mastoid cavity. Diseases of the nose and para nasal sinuses have been implicated in the development of the disease. Hence the present study aims at identifying the risk factors involved and the importance of its management in treating the disease. The objective was to study the correlation between COM and Sino nasal and nasopharyngeal pathology. Methods: A total of 100 patients with chronic otitis media were included in the study. A Detailed history and clinical examination was done using a pre-prepared questionnaire. Diagnostic nasal endoscopy was done in all cases to assess the nasal cavity and nasopharynx along with bacteriological study of ear and corresponding side of nasopharynx. Results: Symptomatic, clinical and diagnostic profile proved the evidence of sinonasal pathology in 82% of patients with COM. The comparative study of the microbiological flora of both ear and corresponding side of nasopharynx showed 77 % of ear swabs and 91% of nasopharyngeal swabs to be sterile. The results were statistically significant with a p value of 0.003. Conclusions: This study emphasises on a thorough evaluation of nose and paranasal sinuses in all cases of COM for comprehensive management of the disease. Its detection and management is equally important as the ear surgery per se.